Hsp70 Is a Potential Therapeutic Target for Echovirus 9 Infection - Wang, Yang; Zhang, Hui; Ma, Dongbo; Deng, Xiang; Wu, Dongdong; Li, Fang; Wu, Qiuge; Liu, Hong; Wang, Jing (Frontiers in Molecular Biosciences, 2020)
Echovirus is an important cause of viral encephalitis in infants, neonates, and young children worldwide. However, the exact mechanism of its pathogenesis is still not well understood. Here, we established an echovirus type 9 infection mice model, and performed two-dimensional gel electrophoresis (2DE) and tandem mass spectrometry (MS/MS)-based comparative proteomics analysis to investigate the differentially expressed host proteins in mice brain. A total of 21 differentially expressed proteins were identified by MS/MS. The annotation of the differentially expressed proteins by function using the UniProt and GO databases identified one viral protein (5%), seven cytoskeletal proteins (33%), six macromolecular biosynthesis and metabolism proteins (28%), two stress response and chaperone binding proteins (9%), and five other cellular proteins (25%). The subcellular locations of these proteins were mainly found in the cytoskeleton, cytoplasm, nucleus, mitochondria, and Golgi apparatus. The protein expression profiles and the results of quantitative RT-PCR in the detection of gene transcripts were found to complement each other. The differential protein interaction network was predicted using the STRING database. Of the identified proteins, heat shock protein 70 (Hsp70), showing consistent results in the proteomics and transcriptomic analyses, was analyzed through Western blotting to verify the reliability of differential protein expression data in this study. Further, evaluation of the function of Hsp70 using siRNA and quercetin, an inhibitor of Hsp70, showed that Hsp70 was necessary for the infection of echovirus type 9. This study revealed that echovirus infection could cause the differential expression of a series of host proteins, which is helpful to reveal the pathogenesis of viral infection and identify therapeutic drug targets. Additionally, our results suggest that Hsp70 could be a useful therapeutic host protein target for echovirus infection.